Load cell adoption in an electronic drag force flowmeter (Scientia Agricola, 2011)
This research introduces the development of an electronic flowmeter based on the drag force that a body experiences when immersed in a fluid stream. Its main goal was the development of an Electronic Drag Force Flowmeter (EDFF) using a load cell, as well as the evaluation of its performance parameters. The developed flowmeter should not require specialized labor, equipments, computers or any sophisticated and complex method, providing an easy and accurate way of flow estimation. This research was carried out in the following stages: (i) EDFF mechanical structure development; (ii) data acquisition system and embedded software design; and (iii) evaluation of EDFF performance parameters. EDFF has routines for instantaneous flow rate measurement, interactive calibration, and also several flow meter parameter adjustments, allowing data transmission via a RS232 protocol. The real-time flow measurement task updates values of instantaneous flow rate each seven seconds, enabling unit selection. The interactive calibration routine guides users during all calibration process showing instructions on EDFF's display. A data digital filtering procedure was implemented in an embedded software using the Grubbs' Test in order to identify and to remove outliers from the acquired data. The Method of Least Squares was also implemented in the embedded software in order to calculate the fitting model coefficients on the calibration procedure. This flowmeter is able to work from 1.94 to 7.78 dm³ s-1 with an uncertainty of ± 5.7%. The coefficient of local head loss (K) was close to 0.55 for Reynolds number values higher than 10(5). The developed EDFF is a low-cost and stand-alone system with potential for agricultural applications.